2001
DOI: 10.1007/s003300000745
|View full text |Cite
|
Sign up to set email alerts
|

International investigation of breast MRI: results of a multicentre study (11 sites) concerning diagnostic parameters for contrast-enhanced MRI based on 519 histopathologically correlated lesions

Abstract: A multicentre study was undertaken to provide fundamentals for improved standardization and optimized interpretation guidelines of dynamic contrast-enhanced MRI. Only patients scheduled for biopsy of a clinical or imaging abnormality were included. They underwent standardized dynamic MRI on Siemens 1.0 (163 valid lesions > or = 5 mm) or 1.5 T (395 valid lesions > or = 5 mm) using 3D fast low-angle shot (FLASH; 87 s) before and five times after standardized bolus of 0.2 mmol Gd-DTPA/kg. One-Tesla and 1.5 T data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
3
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(89 citation statements)
references
References 33 publications
3
77
3
6
Order By: Relevance
“…They observed delayed inflow ICG into the malignant breast lesions compared with benign lesions and non-diseased glandular tissue. This observation contradicts our results obtained with fast optical measurement and also the faster inflow of Gd-DTPA into malignant breast lesions on MRI [87].…”
Section: Indocyanine Green As a Fluorescence Contrast Agentcontrasting
confidence: 99%
See 1 more Smart Citation
“…They observed delayed inflow ICG into the malignant breast lesions compared with benign lesions and non-diseased glandular tissue. This observation contradicts our results obtained with fast optical measurement and also the faster inflow of Gd-DTPA into malignant breast lesions on MRI [87].…”
Section: Indocyanine Green As a Fluorescence Contrast Agentcontrasting
confidence: 99%
“…It is known from breast MRI that analysis of early contrast medium dynamics can provide crucial information for the differentiation between malignant and benign breast lesions [85][86][87]: malignant breast lesions tend to enhance much faster than benign lesions within the first minute of contrast medium administration. In optical mammography, analysis of early and very early contrast enhancement is of interest for the following reasons: 1) Despite ongoing technical developments in MR imaging, the temporal resolution achieved is still lower than that of optical techniques [88,89].…”
Section: Indocyanine Green As An Contrast Agent To Enhance Absorptionmentioning
confidence: 99%
“…Contrast-enhanced magnetic resonance imaging (MRI) has been shown to have a high sensitivity (86% to 100%) for detecting breast cancer in high-risk asymptomatic and symptomatic women, although reports of specificity have been more variable (37% to 97%). [23][24][25][26][27] The American Cancer Society now recommends MRI screening in addition to mammograms for women who meet at least one of the following conditions 28 :…”
Section: Screening Strategies In High-risk Womenmentioning
confidence: 99%
“…70 However, specificity has generally been lower and more variable and ranges from 37% to 97%. 3 In a study based on 519 histopathologically correlated lesions, Heywang-Köbrunner and colleagues 71 illustrate the relatively high sensitivity and relatively low specificity of MRI of the breast. Although the multicenter study was aimed at improving standardization of imaging parameters and interpretation guidelines, the elegant design of the study demonstrated the relatively low specificity of MRI of the breast and the tradeoff between specificity and sensitivity.…”
Section: Sensitivity and Specificitymentioning
confidence: 99%